2012
DOI: 10.1097/qad.0b013e32835099ae
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary function in individuals with HIV infection in the antiretroviral therapy era

Abstract: Objective To determine relationship of echocardiographic measures of pulmonary hypertension to lung function and inflammatory biomarkers in HIV-infected individuals. Design Cross-sectional study of 116 HIV-infected outpatients. Methods Doppler-echocardiography and pulmonary function testing were performed. Induced sputum and plasma cytokines, sputum cell counts and differentials, markers of peripheral T cell activation, and serum N-terminal pro-brain natriuretic peptide (NT-proBNP) were measured. Univariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 50 publications
2
86
3
Order By: Relevance
“…Morris and colleagues recently reported for the first time a link between echocardiographic manifestations related to pulmonary vascular disease and the inflammatory phenotype in HIV-infected individuals (49). Consistent with these observations, we also found significantly increased perivascular cell infiltrates around remodeled vessels in addition to a trend toward up-regulation of proinflammatory mediators such as MCP-1 and IL-8 in the VM group.…”
Section: Discussionsupporting
confidence: 79%
“…Morris and colleagues recently reported for the first time a link between echocardiographic manifestations related to pulmonary vascular disease and the inflammatory phenotype in HIV-infected individuals (49). Consistent with these observations, we also found significantly increased perivascular cell infiltrates around remodeled vessels in addition to a trend toward up-regulation of proinflammatory mediators such as MCP-1 and IL-8 in the VM group.…”
Section: Discussionsupporting
confidence: 79%
“…For example, in a cohort of HIV-infected outpatients, we found that pulmonary function is significantly associated with multiple aspects of cardiovascular disease, including coronary artery calcification and echocardiographic evidence of pulmonary hypertension (17; Morris, unpublished data). HIV-infected participants with elevated pulmonary artery pressures on echocardiography (defined as tricuspid regurgitant jet velocity [TRV] > 3.0 m/s) had significantly worse airflow (17). This relationship with abnormal lung function was similar with pulmonary artery systolic pressure (PASP).…”
Section: Effects Of Systemic Infection Hiv As a Representative Infectionmentioning
confidence: 58%
“…An example of one such infection is HIV. Lung and cardiac diseases, including CVD and pulmonary hypertension, have been reported to be accelerated in individuals with HIV and seem to occur together (16)(17)(18)(19)(20). For example, in a cohort of HIV-infected outpatients, we found that pulmonary function is significantly associated with multiple aspects of cardiovascular disease, including coronary artery calcification and echocardiographic evidence of pulmonary hypertension (17; Morris, unpublished data).…”
Section: Effects Of Systemic Infection Hiv As a Representative Infectionmentioning
confidence: 88%
See 1 more Smart Citation
“…Injection Drug Use as a "Second Hit" in the Pathogenesis of HIV-associated Pulmonary Hypertension HIV-associated pulmonary arterial hypertension (HIV-PAH) is a serious complication that develops in approximately 1:200 of HIV-infected individuals, and an even higher prevalence of echocardiographic signs of pulmonary hypertension indicates that the disease may be more common than previously thought (1)(2)(3). Mortality is high, even in the era of antiretroviral therapy (ART) (4).…”
mentioning
confidence: 99%